Evaluación de metabolitos secundarios y propiedades antioxidantes e hipoglucemiante de lúcuma (Pouteria lucuma) en dos estados de madurez - Mejía Rios, Claudia Vanessa (2017)
The lucuma (Pouteria lúcuma) is a subtropical fruit of Andean origin. Traditionally appreciated for its sensory characteristics and its versatility for the food industry. In the present investigation, an identification and quantification of the main secondary metabolites in lucuma of the "Dos Marrón" biotype in two stages of maturity (green and purple) was carried out, as well as an analysis of the hydrophilic and lipophilic antioxidant capacity. Additionally, the hypoglycaemic activity was evaluated by the inhibition of a-amylase and a-glucosidase in both states. It was found that the state of maturity of the fruit influences the content of secondary metabolites, observing that the lucuma in the green state had higher concentrations of phenolic compounds and tocopherols, while the lucuma in the green state had the highest amount of carotenoids (p <0,05). The chromatographic analysis revealed that the major phenolic compounds belong to the family of flavanols and flavanones; as for carotenoids, the xanthophylls were predominant and a-tocopherol was the most abundant tocopherol. The chromatographic profiles found in all the bioactive compounds evaluated were similar for both maturity stages; differing only at the level of concentrations; while for the phytosterols, no statistical differences were found (p > 0,05). Regarding the antioxidant and hypoglycaemic capacity, significant differences were reported (p <0,05) in the hydrophilic antioxidant capacity measured by the ABTS and ORAC assays and inhibition of the a-glucosidase; however, no significant differences were found in the lipophilic antioxidant activity or in the inhibition of a-amylase between both maturity stages. These results show that lucuma in both states is an interesting source of functional bioactive compounds with potential application in the food industry